Tribes & Cultures – Cross-disciplinary Communication: Pinpointing the Issues for eLearning - Dreher, Naomi; Dreher, Heinz (University of Maribor, 2011)
Effective communication and co-operation across disciplines is needed to create and deploy eLearning systems so that they contribute to enhanced outcomes for students and teachers. Using a Grounded Theory methodology we probed the cultures of the participating tribes: the Educationalists; the Instructional Designers; and the Information Technology Specialists. Six salient themes emerged from the semi-structured interview data of respondents selected from the three tribes, each of which is described in detail in this article. These themes give rise to Six Rules of Thumb to help promote fruitful communication and interaction among the tribes and cultures of eLearning system stakeholders, and thus result in improved eLearning systems.